2020
DOI: 10.1038/s41598-020-79065-9
|View full text |Cite
|
Sign up to set email alerts
|

Serum amyloid A is a positive acute phase protein in Russian sturgeon challenged with Aeromonas hydrophila

Abstract: The immune system of sturgeons, one of the most ancient and economically valuable fish worldwide, is poorly understood. The lack of molecular tools and data about infection biomarkers hinders the possibility to monitor sturgeon health during farming and detect infection outbreaks. To tackle this issue, we mined publicly available transcriptomic datasets and identified putative positive acute-phase proteins (APPs) of Russian sturgeons that could be induced by a bacterial infection and monitored using non-invasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 111 publications
(81 reference statements)
1
18
0
Order By: Relevance
“…Although transcript levels of most inflammatory mediators were similar between treatments, transcript expression of acute phase proteins were higher in the gills of β-glucan-fed fish challenged with F. columnare at one dpc compared to other treatments. Serum amyloid A and haptoglobin are some of several acute-phase proteins generated early in the initial immune response to infection [ 45 , 46 ] which coincides with the one dpc increase observed in this study. Previous studies have showed increasing levels of haptoglobin expression after bacterial infection suggesting an important role preventing iron loss as a hemoglobin scavenger [47] .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Although transcript levels of most inflammatory mediators were similar between treatments, transcript expression of acute phase proteins were higher in the gills of β-glucan-fed fish challenged with F. columnare at one dpc compared to other treatments. Serum amyloid A and haptoglobin are some of several acute-phase proteins generated early in the initial immune response to infection [ 45 , 46 ] which coincides with the one dpc increase observed in this study. Previous studies have showed increasing levels of haptoglobin expression after bacterial infection suggesting an important role preventing iron loss as a hemoglobin scavenger [47] .…”
Section: Discussionsupporting
confidence: 83%
“…Previous studies have showed increasing levels of haptoglobin expression after bacterial infection suggesting an important role preventing iron loss as a hemoglobin scavenger [47] . Similarly, saa’s role early in infection as pro-inflammatory regulator is well studied in mammals and fish [ 46 , 48 ]. Serotransferrin plays a crucial role in regulating availability of iron during infection and immunostimulation of macrophages and other inflammatory responses [39] .…”
Section: Discussionmentioning
confidence: 99%
“…128 Also, in sturgeon challenged with the same infectious agent, SAA was highly upregulated. 129 In the koi carp, an albumin migrating fraction was recognized as well as at least four other fractions using AGE and changes in fractions were seen in some fish after exploratory coeliotomy. 130 Using CAE, the fractions were found to be quite variable among normal koi in one study but not in a second report.…”
Section: Teleos T S Pecie Smentioning
confidence: 97%
“…However, interpreting EPH profiles with regard to health remains challenging, and further investigation is warranted, including determination of which proteins constitute EPH fractions in pompano and other teleosts. TTR, albumin‐like proteins (high‐density lipoproteins), alpha‐1 globulins (alpha‐1‐antitrypsin, transcortin, alpha‐1‐acid glycoprotein, and apolipoprotein‐A1), alpha‐2 globulins (acute phase proteins [APP], ceruloplasmin, haptoglobin, and alpha‐2‐macroglobulin), beta‐globulins (transferrin, angiostatin, hemopexin, beta‐2‐microglobulin, properdin, and low‐density beta‐lipoproteins), and gamma globulins (IgM, IgD, IgT/Z, fibrinogen, and c‐reactive protein) have all been identified in teleosts, but further research is needed to identify these proteins in Florida pompano and determine their patterns of fractionation (Andreeva et al, 2020; Bilal et al, 2021; Castellano et al, 2020; Charlie‐Silva et al, 2019; Pérez‐Sánchez et al, 2017; Power et al, 2000; Yamauchi, 2021).…”
Section: Discussionmentioning
confidence: 99%